Analisis Sentimen Wacana Penerapan Jalan Berbayar di Jakarta Menggunakan Algoritma SVM - Ahmad Fauzi; Eko harli; Tria Hadi Kusmanto (STMIK Budi Darma, 2023)
Traffic congestion is a serious problem faced by major cities worldwide, including Jakarta. One effort to address traffic congestion in Jakarta is by implementing Electronic Road Pricing (ERP) on certain road sections. The proposal for implementing ERP is a controversial policy in Jakarta, and understanding the sentiment of the community regarding this policy is crucial for decision-making. Twitter, as the largest social media platform, serves as a platform for the public to voice their opinions regarding this policy. This research aims to analyze the discourse sentiment related to the implementation of ERP in Jakarta using the Support Vector Machine (SVM) algorithm. The sentiment data used consists of positive and negative sentiments. The research results show that the SVM algorithm achieved an accuracy rate of 81%, precision of 83%, and recall of 85%.